Paleodepth determination from Antarctic benthic diatom assemblages - Whitehead, JM; Andrew McMinn (1997)
Analysis of modem surface sediments from fjords in the Vestfold Hills (Antarctica) indicates that 58% of the variation in benthic diatom assemblages can be attributed to changes in environmental parameters with water depth. Attenuation of light through the water column is suggested to account for 45% of the variation, and the decrease in substrate grain size with depth possibly accounts for a further 13%. Cluster analysis and principal component analysis were used to objectively circumscribe five floral zones between the surface and 35 m depth. The depth distribution of the benthic diatoms was then used to interpret the paleodepth of relict fjord (Holocene) sediments exposed around Deep Lake in the Death Valley (Vestfold Hills). Paleodepths measured from the sea-ice bench around Deep Lake combined with data from grain size analysis indicate that the relict fjord sediments have no analogue amongst the modem fjord sediments sampled in the Vestfold Hills. Without a comparable modem habitat on which to model the diatom depth zones, however, this study was unable to accurately determine the paleowater depth at Deep Lake using diatoms. Paleodepth determination will be possible using grain size analysis and diatom dam when the substrate and light requirements of benthic diatoms are understood.